Integrated Assessment of Ocean Acidification Risks to Pteropods in the Northern High Latitudes: Regional Comparison of Exposure, Sensitivity and Adaptive Capacity - Bednaršek, Nina; Naish, Kerry-Ann; Feely, Richard A.; Hauri, Claudine; Kimoto, Katsunori; Hermann, Albert J.; Michel, Christine; Niemi, Andrea; Pilcher, Darren (Frontiers in Marine Science, 2021)
Exposure to the impact of ocean acidification (OA) is increasing in high-latitudinal productive habitats. Pelagic calcifying snails (pteropods), a significant component of the diet of economically important fish, are found in high abundance in these regions. Pteropods have thin shells that readily dissolve at low aragonite saturation state (Ωar), making them susceptible to OA. Here, we conducted a first integrated risk assessment for pteropods in the Eastern Pacific subpolar gyre, the Gulf of Alaska (GoA), Bering Sea, and Amundsen Gulf. We determined the risk for pteropod populations by integrating measures of OA exposure, biological sensitivity, and resilience. Exposure was based on physical-chemical hydrographic observations and regional biogeochemical model outputs, delineating seasonal and decadal changes in carbonate chemistry conditions. Biological sensitivity was based on pteropod morphometrics and shell-building processes, including shell dissolution, density and thickness. Resilience and adaptive capacity were based on species diversity and spatial connectivity, derived from the particle tracking modeling. Extensive shell dissolution was found in the central and western part of the subpolar gyre, parts of the Bering Sea, and Amundsen Gulf. We identified two distinct morphotypes: L. helicina helicina and L. helicina pacifica, with high-spired and flatter shells, respectively. Despite the presence of different morphotypes, genetic analyses based on mitochondrial haplotypes identified a single species, without differentiation between the morphological forms, coinciding with evidence of widespread spatial connectivity. We found that shell morphometric characteristics depends on omega saturation state (Ωar); under Ωar decline, pteropods build flatter and thicker shells, which is indicative of a certain level of phenotypic plasticity. An integrated risk evaluation based on multiple approaches assumes a high risk for pteropod population persistence with intensification of OA in the high latitude eastern North Pacific because of their known vulnerability, along with limited evidence of species diversity despite their connectivity and our current lack of sufficient knowledge of their adaptive capacity. Such a comprehensive understanding would permit improved prediction of ecosystem change relevant to effective fisheries resource management, as well as a more robust foundation for monitoring ecosystem health and investigating OA impacts in high-latitudinal habitats.